A Bibliometric Analysis of Research on Academic Buoyancy - Dewi, Innayah Kusuma; Izzaty, Rita Eka; Sarjana, Sri; Roehan, Muhammad Sani (Universitas Mercu Buana Jakarta, 2025)
Academic buoyancy is a positive psychology construct that is the ability to bounce back from academic challenges and obstacles that individuals commonly experience on a daily basis. The purpose of this study is to determine the trend of research mapping related to academic buoyancy using bibliometric analysis and to recognize the novelty of topics that can later be studied by future researchers. The method used in this research is a systematic literature review with bibliometric analysis. Data collection was carried out in April 2025 with the Publish or Perish (PoP) application and using a database from Google Scholar with the keyword academic buoyancy in scientific journal publications in 2015-2024 so that 994 scientific journals were obtained. In VOSviewer bibliometric analysis, researchers conduct data analysis and visualization starting from the analysis of the topics studied, network visualization analysis, overlay visualization, density visualization, and connected authorship visualization. The results of the bibliometric analysis with the keyword academic buoyancy obtained novelty findings in this study, namely topics related to peers, positive youth development, classroom environment, mattering, self-efficacy, school burnout, achievement motivation, academic buoyancy scale. Some of these research topics can be used as suggestions for future researchers to further develop academic buoyancy derived topics in order to disseminate and strengthen knowledge development that has the potential to foster innovation and novelty